Efektivitas Daun Mengkudu (Morinda citrifolia) sebagai Insektisida Nabati Terhadap Hama Kutu Putih (Paracoccus marginatus): Effectiveness Of Mengkudu Leaves (Morinda citrifolia) As A Plant-based Insecticide Against Kutu Putih Pest (Paracoccus marginatus) - Pebriandi; Silitonga, Ester Marisi; Mardhiansyah, Muhammad; Oktorini, Yossi; Somadona, Sonia; Irfani, Ewi (Jurnal Ilmu Ilmu Kehutanan, 2025)
The decline in productivity of Acacia seedlings (Acacia crassicarpa) in Industrial Plantation Forests is caused in part by attacks of mealybug pests (Paracoccus marginatus). Using chemical insecticides in pest control can negatively impact health and the environment, so more environmentally friendly alternatives are needed, such as plant-based insecticides. This study aims to determine the concentration of noni leaf extract on the mortality of mealybug pests. A completely randomized design (CRD) was employed, consisting of four treatments with different concentrations of Morinda citrifolia leaf extract (30 g/l, 40 g/l, 50 g/l, and 60 g/l), each replicated three times. The observed parameters included the time of initial death, Lethal Time 50 (LT₅₀), and total mortality percentage. The results indicated that the use of Morinda citrifolia leaf extract of 60 g/l was the most effective, with an average time of 8,67 hours, LT₅₀ of 24,67 hours, and total mortality rate of 100% for Paracoccus marginatus.